7t-(t-4)=25

Simple and best practice solution for 7t-(t-4)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7t-(t-4)=25 equation:


Simplifying
7t + -1(t + -4) = 25

Reorder the terms:
7t + -1(-4 + t) = 25
7t + (-4 * -1 + t * -1) = 25
7t + (4 + -1t) = 25

Reorder the terms:
4 + 7t + -1t = 25

Combine like terms: 7t + -1t = 6t
4 + 6t = 25

Solving
4 + 6t = 25

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6t = 25 + -4

Combine like terms: 4 + -4 = 0
0 + 6t = 25 + -4
6t = 25 + -4

Combine like terms: 25 + -4 = 21
6t = 21

Divide each side by '6'.
t = 3.5

Simplifying
t = 3.5

See similar equations:

| (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 | | 6-0.25f=3 | | 6.4x=0.2816 | | -6t+17=3t-34 | | -23z+234=970 | | 0.4y-8=9-0.6y | | .01x+.10x+.25(31-2x)=3.46 | | 108+4u=2u | | -.8x+2.2=7 | | 5x+21-2x=27 | | -3.7-5x-8.3-2x=-6x+11.4 | | 6.4x=0.2016 | | 4a^2-10=54 | | (72.34)2.1= | | -3(3x+15)-(10-1x)=35 |

Equations solver categories